Diversified applications of hepatocellular carcinoma medications: molecular-targeted, immunotherapeutic, and combined approaches - Chen, Haoyang; Liu, Huihui; Zhang, Xiaowei; Wang, Suhua; Liu, Chunxia; An, Ke; Liu, Ruijuan; Tian, Xin (Frontiers in Pharmacology, 2024)
Hepatocellular carcinoma (HCC) is one of the primary forms of liver cancer and is currently the sixth most prevalent malignancy worldwide. In addition to surgical interventions, effective drug treatment is essential for treating HCC. With an increasing number of therapeutic drugs for liver cancer undergoing clinical studies, the therapeutic strategies for advanced HCC are more diverse than ever, leading to improved prospects for HCC patients. Molecular targeted drugs and immunotherapies have become crucial treatment options for HCC. Treatment programs include single-agent molecular-targeted drugs, immunotherapies, combinations of immunotherapies with molecular-targeted drugs, and dual immune checkpoint inhibitors. However, further exploration is necessary to determine the optimal pharmacological treatment regimens, and the development of new effective drugs is urgently needed. This review provides an overview of the current globally approved drugs for liver cancer, as well as the latest advances in ongoing clinical research and drug therapies. Additionally, the review offers an outlook and discussion on the prospects for the development of drug therapy approaches for HCC.